2021
DOI: 10.1002/zaac.202000436
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Coordination Behaviour of a Novel Tridentate P,N,O‐Ketiminate Ligand

Abstract: Treatment of o-(diphenylphosphino)aniline with 3-formylacetylacetone led to the formation of the ketimine type Schiff base 3-((o-diphenylphosphino-phenylamino)-methylene)-pentane-2,4-dione (oÀ PPh 2 À C 6 H 4 À NHÀ CH=C(COCH 3 ) 2 , HL). Complexes [ML 2 ] (M = Fe, Co, Ni, Cu) were obtained from the reaction of HL with the corresponding metal acetate or acetylacetonate derivatives. The [ML 2 ] complexes (M = Fe, Co, Ni) exhibit a distorted octahedral coordination from two tridentate P,N,O ketiminate ligands L À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These values are close to those found in the parent compound amino-methylene-pentane-2,4-dione (1.397 and 1.304 A ˚, respectively; Gro ´f et al, 2006a) and in the related NMe derivative (1.405 and 1.309 A ˚, respectively; Gro ´f et al, 2006b). The same holds for the corresponding Schiff bases derived from isomeric o-, m-and p-aminobenzoic acids (Halz et al, 2022), -amino acids (Hentsch et al, 2014) or o-diphenylphosphinoaniline (Halz et al, 2021). In summary, these observations clearly indicate that the R group attached to the enamine N atom has no significant influence on the bond lengths and angles of the amino-methylene-pentane-2,4-dione moiety.…”
Section: Structural Commentarymentioning
confidence: 60%
See 1 more Smart Citation
“…These values are close to those found in the parent compound amino-methylene-pentane-2,4-dione (1.397 and 1.304 A ˚, respectively; Gro ´f et al, 2006a) and in the related NMe derivative (1.405 and 1.309 A ˚, respectively; Gro ´f et al, 2006b). The same holds for the corresponding Schiff bases derived from isomeric o-, m-and p-aminobenzoic acids (Halz et al, 2022), -amino acids (Hentsch et al, 2014) or o-diphenylphosphinoaniline (Halz et al, 2021). In summary, these observations clearly indicate that the R group attached to the enamine N atom has no significant influence on the bond lengths and angles of the amino-methylene-pentane-2,4-dione moiety.…”
Section: Structural Commentarymentioning
confidence: 60%
“…This is easily done by the reaction of 3-formylacetylacetone with a suitably functionalized amine, e.g. in form of -amino acids (Hentsch et al, 2014) or o-diphenylphosphinoaniline (Halz et al, 2021).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Recently, this type of ligand was applied successfully for the preparation of Fe II complexes that exhibit spin-crossover effects (Dankhoff & Weber, 2019). In a previous study, we were interested in the preparation of chiral N,O,O-ketiminate ligands from 3-formylacetylacetone and naturally occuring aminoacids (Hentsch et al, 2014) and recently, we reported on N,O,Pketiminates with additional PPh 2 functionalities (Halz et al, 2021). In this context, we studied the synthesis of Schiff bases derived from 3-formylacetylacetone and the isomeric o-, mand p-aminobenzoic acids.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Complexes of the type [M(acac) 2 (TMEDA)] (acac is acetylacetonate, TMEDA is tetramethylethylenediamine) are valuable starting materials for the preparation of coordination compounds (Kaschube et al, 1988;Nelkenbaum et al, 2005;Albrecht et al, 2019;Halz et al, 2021). Recently, we reported on the crystal structures of three complexes [M(acac) 2 (TMEDA)] with M = Mn, Fe, Zn (Halz et al, 2020), and in the course of these studies we were interested in a structure determination of the magnesium analogue from X-ray data.…”
Section: Structure Descriptionmentioning
confidence: 99%